2019
DOI: 10.1111/jace.16848
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electromagnetic wave absorption of Fe‐doped silicon oxycarbide nanocomposites

Abstract: Polymer‐derived ceramics (PDCs), such as SiOC, SiCN, SiBCN, and SiC are considered the best candidates for designing high‐performance microwave absorber due to their controllable structure, homogeneous element composition at atom level, tunable electromagnetic and electrochemical properties. Herein, Fe ions doped silicon oxycarbide (Fe ions‐SiOC) ceramics have been successfully fabricated via solvothermal method. The electromagnetic absorption performances of the nanocomposites prove to be controllable via tai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 66 publications
(135 reference statements)
0
15
0
Order By: Relevance
“…The materials with 5 vol% graphene exhibit a large tanδ ranging from 0.9 to 1.2. According to previous studies, 35,42,43 materials with good dielectric properties and a dielectric loss tangent are suitable electromagnetic shielding materials. As the graphene embedded in MgO play a crucial role in changing the complex permittivity, these graphene/MgO composites are potential EMI shielding materials in the X-band.…”
Section: Dielectric Properties and Emi Se In The X-band Frequency Rangementioning
confidence: 99%
“…The materials with 5 vol% graphene exhibit a large tanδ ranging from 0.9 to 1.2. According to previous studies, 35,42,43 materials with good dielectric properties and a dielectric loss tangent are suitable electromagnetic shielding materials. As the graphene embedded in MgO play a crucial role in changing the complex permittivity, these graphene/MgO composites are potential EMI shielding materials in the X-band.…”
Section: Dielectric Properties and Emi Se In The X-band Frequency Rangementioning
confidence: 99%
“…Overall, the enhanced EMW absorption properties might be mainly due to the matched impedance and improved loss ability that arose from the synergetic effect among carbon fibers, BPR-derived carbon, and SiOC ceramic. To date, lots of efforts have been made to investigate and improve the EMW absorption properties of carbon fibers and PDCs, especially in construction of composites, and thus we further compared the EMW absorption capabilities between our products and absorbers recently reported and the results were displayed in Figure 10 and Table S2 [6,[9][10][11][12][13][15][16][17][18][19][20][24][25][26]. Although the RL min value for our products, namely BPR-derived carbon modified 3D needled carbon fiber reinforced SiOC composites is not the lowest, the value is comparable to those of most of PDCs (Figure 10a).…”
Section: Influence Of Pip Cycle Numbers On the Microstructure And Promentioning
confidence: 99%
“…From the ceramic point of view, polymer-derived ceramics (PDCs) have gained much attention, which could be attributed to their remarkable properties over conventional ceramics, such as low processing temperature and excellent properties, especially in thermal stability, high-temperature mechanics, and oxidation resistance [9,10]. Among all PDCs, apart from the amorphous phase with low thermal conductivity, the low-cost silicon oxycarbide (SiOC) ceramics possess inherent chemical durability, tunable mechanical and unusual high-temperature properties, which should be ascribed to its special structure, namely an anionic silica network, in which, two divalent O atoms are partially replaced by one tetravalent C atom [11][12][13]. Hence, SiOC modified CBCF composites have been constructed and investigated by researchers [14], while there is no report on BPR-derived carbon modified 3D needled carbon fiber reinforced SiOC composites, which according to previous research have superior mechanical and high-temperature properties and could be used in high-temperature applications such as thermal protection systems.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] These Femodified composites were shown to be highly interesting with respect to their magnetic properties 15,[20][21][22][23] or interaction with electromagnetic waves. [24][25][26] It was reported that their temperature-dependent evolution of the phase composition is rather complex and involves the formation of various Fe-containing secondary phases. 13,17,19 In a case study related to a polymer-derived Si-Fe-O-C system, iron(III)acetylacetonate-modified polysiloxane was converted via pyrolysis into a singlephasic amorphous SiFeOC ceramic, which partitioned at relatively low temperature (<900 • C) to generate cementite (Fe 3 C) as a finely dispersed phase within the SiOC matrix.…”
Section: Introductionmentioning
confidence: 99%